ANALISIS NILAI-NILAI PANCASILA DALAM TRADISI PERAHU BAGANDUANG DI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Hamzah, Akmal; Zahirman, Zahirman; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims is to analyzed Pancasila values contained in Perahu Baganduang tradition in Kuantan Mudik district Kuantan Singingi Regency. This research is qualitative research with used an informan choosed by purposive with snowball sampling technique. Informan on this research are traditional leaders, young people which know about perahu baganduang. Data collected technique used are observation, interview, library study, and documentation. Analysis data technique used are data collected, data reduction, data serving and conclusion with verification. The results of this research show that there is a Pancasila value in the tradition of a boat. This can be seen from sila 1: praying before the event begins and its implementation after the five daily prayers, the second is : justice for the whole community by not distinguishing the community group, the third is: the young people who unite and cooperate in making a boat, in sila 4: the formation of the committee and the implementation of the boat event are in accordance with deliberation the decision can take together, the fifth is : social justice which all communities have the same right to make the boat event successful without distinguishing groups. From the results of this research it can be concluded that there is a Pancasila value in the tradition of a baganduang boat in the Kuantan Mudik sub-district of Kuantan Singingi district.Key Words: Analysis of Pancasila Value, Culture, Perahu Baganduang.